Potensi Ekstrak Buah Buni (Antidesma bunius (L) Spreng) Sebagai Inhibitor Enzim α-Glukosidase - La Hamidu; Partomuan Simanjuntak; Rizna Triana Dewi (Jurnal Fitofarmaka Indonesia, 2020)
Diabetes mellitus is still a global health problem that continues to increase rapidly and become one of the major metabolic diseases throughout the world. This study aims to determine the potential of Buni fruit as an α-glucosidase inhibitor. α-glucosidase inhibition test is carried out on a blank solution (test solution without sample/standard), acarbose solution as a comparison standard and samples are carried out in accordance with the optimization conditions obtained. The rendemen percent of green and red buni fruit extract yields are 6.35% and 3.09%, respectively. The results of the identification of secondary metabolites using TLC showed that green and red buni fruit extract contains flavonoid, phenolic and alkaloid compounds. The results of the α-glucosidase enzyme inhibition test showed that the red buni fruit extract had the highest activity compared to green buni fruit extract with an IC50 value of 85.27 ppm.